(3LhGH eSCdI dQLdjf ef Cgd WHQSJGfs - (3CHh eMeO GdbGSe Hf EHQGgje Hf ESeGYjd GdMSfj GdQSj, GdQSj,J (B246 (3g` s
(3ChdgG (B:s
(3SCdJ CHj QMeg Gddg Ydjg (B_ (3dQLdjf ef Cgd WHQSJGf , hgeG Yf JhMjO Gddg heYQaJg , heG ENJda ajg GdeNJdahf ef UaJg , abGd s
(3BNQgG (B:s
(3agPg LhGeY GdEjeGf eY GdEjeGf GdhGLHI GddGReI , GdeTHgI ai Mce Gddg GdJi dG JNJda LedgG , hdG jSY ecdakG LgdgG JeJ s
(3cJHJ GdahGJM HGdSejcs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B171s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds